Estimating the intrahousehold costs and benefits of innovations to enhance smallholder farmers’ resilience - Kramer, Berber; Timu, Anne G.; Damba, Osman (Frontiers Media, 2023)
This paper introduces a new framework to quantify costs and benefits for resilience-related outcomes of agricultural innovations targeting smallholder farmers. The framework employs a non-unitary household model with expected utility to quantify welfare benefits associated with non-monetary outcomes that are important from a development perspective, such as improved consumption smoothing, empowerment, and changes in time use. We demonstrate the application of the framework using a case study of climate information services (CIS) in Ghana. We develop a set of individual bargaining weights based on the women’s empowerment in agriculture index, to demonstrate how benefits from CIS are distributed among men and women within households. We find that for the average risk-averse farmer, using CIS is associated with a 37-percent increase in expected utility, but male household heads benefit more than women living in male-headed households. Cost–benefit analyses that do not consider the intrahousehold distribution of benefits associated with agricultural innovations will overestimate benefits accruing to women with low bargaining power.